2009
DOI: 10.1002/cncr.24346
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular markers of outcome prediction in prostate cancer

Abstract: Prostate cancer has a variable clinical outcome and, therefore, there is a clear need for novel molecular markers that are specifically associated with biologically aggressive disease to improve staging and prognostication and also to provide mechanistic information to facilitate treatment selection. Different candidate biomarkers have been identified that are linked to patient prognosis and/or response to specific treatments. Such molecules are involved in diverse cellular processes (including cell cycle regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Research over the past decade has identified a number of biomarkers that are associated with high Gleason grade disease [7][13]. Previous studies from our laboratory found a correlation between expression of FLICE-inhibitory protein (FLIP) and tumor grade in human prostate cancer [13].…”
Section: Introductionmentioning
confidence: 93%
“…Research over the past decade has identified a number of biomarkers that are associated with high Gleason grade disease [7][13]. Previous studies from our laboratory found a correlation between expression of FLICE-inhibitory protein (FLIP) and tumor grade in human prostate cancer [13].…”
Section: Introductionmentioning
confidence: 93%
“…Current diagnostic methods; measuring levels of prostate specific antigen (PSA) in blood samples and examining needle biopsies from the prostate under light microscopy, are however not particularly effective in separating cases of aggressive PCa from the even more prevalent and indolent forms of PCa that often can be left without treatment, or in separating cancer from other non-malignant prostate disorders [1], [2]. Using a variety of techniques multiple investigators have therefore tried to find novel diagnostic methods and prognostic markers that can separate aggressive from more indolent forms of PCa (reviewed in [3]). …”
Section: Introductionmentioning
confidence: 99%
“…DNA, RNA, and protein markers all hold potential for innovations in prostate cancer screening. The applications of these markers to prostate cancer screening have been extensively reviewed in many studies (Li-Wan-Po et al, 2010;Lopergolo & Zaffaroni, 2009;Martin, Mucci, Loda, & Depinho, 2011;Ploussard & de la Taille, 2010;Urquidi, Rosser, & Goodison, 2012;Witte, 2009). Of these potential tests, only the Prostate Cancer Gene 3 (PCA3) test is commercially available.…”
Section: Development Of Genetic Testing For Prostate Cancermentioning
confidence: 99%